ANALISIS PERKEMBANGAN EKONOMI DIGITAL DALAM MENINGKATKAN DAYA SAING UMKM DAN PERTUMBUHAN EKONOMI DI INDONESIA - Nansadiqa, Lisa (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2026)
Digitalization has contributed significantly to increasing economic growth in Indonesia through increased productivity, job creation, and expanding financial inclusion, especially for Micro, Small, and Medium Enterprises (MSMEs). However, the digital transformation of Micro, Small, and Medium Enterprises (MSMEs), especially in Banda Aceh City, is crucial in adapting to challenges and opportunities in the era of disruption. The purpose of this research is to determine the development and impact of the digital economy in increasing the competitiveness of MSMEs and economic growth in Indonesia, especially in the city of Banda Aceh. The purpose of this research is to determine the development and impact of the digital economy in increasing the competitiveness of MSMEs and economic growth in Indonesia, especially in the city of Banda Aceh. This study uses a descriptive qualitative method based on literature studies to analyze the development of the digital economy in increasing the competitiveness of MSMEs and economic growth in Indonesia. The results of the analysis show that the digital economy not only increases economic efficiency but also encourages the emergence of new business models or increases the competitiveness of MSMEs that are more adaptive to technological changes, thereby driving economic growth in Indonesia. Support from the government and all stakeholders is highly expected through pro-digitalization policies, increasing digital literacy, and infrastructure development as key factors in creating an inclusive and sustainable digital economic ecosystem. Overall, the digital economy plays a vital role in Indonesia's economic transformation towards the Industry 5.0 era.